Livre concorrência, tributação e desenvolvimento socioeconômico: utilização de legítimas vantagens tributárias em prejuízo da livre concorrência - Campanile, Vinicius Tadeu (2017)
This dissertation aims to analyze the behavior of economic agents in the relevant markets in which they operate, especially considering the possibility and enjoyment of tax advantages which may be considered legitimate, but should not serve as a guarantee for privileges for those who in detriment of the competition. This is because taxation causes unavoidable impacts on the economy and a full understanding of the phenomenon is not possible without due consideration of the related market issues, particularly the analysis of the points of contact between taxation and competition and it is necessary to establish a dialogue between these systems, which today are complementary and inseparable. The task of confronting and analyzing the problem and the relationship between taxation and, particularly, its effects on free competition, and its important consequences for Brazilian economic and social development, is only feasible with the adoption of a vision broader scope of the Tax Law, which understands it in an interdisciplinary and systematic way. In view of this situation and the numerous competitive effects in tax matters, the study focuses on the conduct of these agents and their limits, in a way in which freedom of initiative, free competition, the social function of ownership of production assets, the principle of the neutrality of taxation and the principle of equality impose on them, in view of the principles, values and commitments demanded by the present constitutional order, with the social actors having as their duty a real social transformation.